2018
DOI: 10.1186/s13293-018-0198-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and preclinical evidence of sex-related differences in anthracycline-induced cardiotoxicity

Abstract: Anthracyclines are very effective chemotherapeutic agents that are widely used to treat pediatric and adult cancer patients. Unfortunately, the clinical utility of anthracyclines is limited by cardiotoxicity. There are several established risk factors for anthracycline-induced cardiotoxicity (AIC), including total cumulative dose, very young and very old age, concomitant use of other cardiotoxic agents, and concurrent mediastinal radiation. However, the role of sex as a risk factor for AIC is not well defined.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 86 publications
0
45
1
Order By: Relevance
“…Indeed, nutraceuticals with anti-inflammatory properties such as lycopene, curcumin, and resveratrol have been shown to reduce the toxicity and improve the efficacy of chemotherapeutic agents [14,27]. We and others have reported significant sex-related differences in acute and chronic DOX-induced cardiotoxicity and nephrotoxicity in experimental animals [11,[28][29][30][31][32]. Sexual dimorphism of acute DOX-induced cardiotoxicity is associated with higher expression of inflammatory genes in the heart of male than female mice [11].…”
Section: Discussionmentioning
confidence: 83%
“…Indeed, nutraceuticals with anti-inflammatory properties such as lycopene, curcumin, and resveratrol have been shown to reduce the toxicity and improve the efficacy of chemotherapeutic agents [14,27]. We and others have reported significant sex-related differences in acute and chronic DOX-induced cardiotoxicity and nephrotoxicity in experimental animals [11,[28][29][30][31][32]. Sexual dimorphism of acute DOX-induced cardiotoxicity is associated with higher expression of inflammatory genes in the heart of male than female mice [11].…”
Section: Discussionmentioning
confidence: 83%
“…findings of this study is the sex-dependent differences in cardiotoxicity and survival. Notably, clinical data showed that the male sex is a risk factor for adverse cardiac effects in adult patients undergoing anthracycline therapy (26). Consistently, regardless of genotype, male mice treated with DOX displayed an average of 45% survival rate 5 days post-DOX while in females groups an average of 86% mice survived this time period.…”
Section: Sex-dependent Differences In Doxorubicin Cardiotoxicity: Onementioning
confidence: 84%
“…In previous studies among paediatric cancer survivors, female sex has repeatedly been associated with an increased risk of anthracycline-related LV dysfunction 31 . In adults, this relation has been inconclusive, probably because a majority of studies concerning cardiotoxicity have been performed in female breast cancer patients.…”
Section: Discussionmentioning
confidence: 95%